A Plant design for plywood adhesives and molding powder based on phenol-formaldehyde resins - Angeles, Mariano A. (College of Engineering, 1973)
Plant: Phenol-Formaldehyde -- Site: Limay, Bataan -- Plant site area: 3,420 sq. meters -- Main raw materials: Phenol, Formaldehyde -- Secondary raw materials: Wood flour, Hexamethylenetetramine,, Sulfuric acid, Sodium Hydroxide, Nigrosin Dye, Calcium Stearate -- Plant operation: 24 hr/day at 300 days/yr -- Plant capacity: 33,854 tons/yr -- Fixed capital: 46,907,000 -- Total capital investment: 53,942,000 -- Total cost: 104,074,650 -- Annual sales: 120,000,000 -- Gross profit: 15,925,350 -- Net profit: 7,675,350 -- Percent rate of return based on fixed capital: 16.4% -- Percent rate of return based on total capital investment: 14.25% -- Break-even point: 52% -- Shut-down point: 32.6% -- Pay-out time: 6.12 years